Pengaruh Gaya Hidup Dan Harga terhadap Minat Beli pada Matahari Departemen Store Mal Festive Walk Dimasa Pandemi Covid-19 Studi Kasus pada Generasi Z di Kabupaten Karawang - Hadiana Maulidia Anaya Kusumah; Cecep Hermana (STIE AMKOP, 2022)
Abstrak This study aimed to examine and analyse the Effect of Lifestyle and Prices on Buying Interest at Matahari Department Store Mall Festive Walk During the Covid-19 Pandemic (Case Study on Generation Z in Karawang Regency).This research was conducted using quantitative methods with descriptive and verificative. The sampling techniques applied non-probability sampling using random sampling, resulting in 400 samples from a population of 634,306 generation Z in Karawang Regency. The analytical technique adopted in this examination was the scale-range analysis and path analysis with the help of the Microsoft Excel 2013 computer program and the SPSS version 22 application.The results of this study indicated that the influence of lifestyle and price had a strong correlation of 0.745. The partial effect of lifestyle on purchasing interest is 38.9%, whereas the price of purchasing interest is 32%. Simultaneously, lifestyle and price influence 70.9 % of buying interest; on the other hand, the remaining 29.1% was influenced by factors not investigated. Keywords: Lifestyle_1, Price_2, Buying Interest_3.